Efektivitas Aplikasi Larvasida Temephos 1% Sistem Membran dan Sistem Tabur Terhadap Larva Aedes sp - Dina Merlyaningrum; Sarjito Eko Windarso; Indah Werdiningsih (Sanitasi: Jurnal Kesehatan Lingkungan, 2016)
Dengue haemorrhagic fever is a dangerous disease because may lead to death within a relatively short time. The disease is caused by dengue virus that enters human body through the bite of Aedes sp mosquitoes. DHF prevention activity is done by sowing larvicidal granule in water reservoirs that are difficult to clean. Larvicide that is often used by people to eradicate Aedes sp larvae is abate (temephos 1 %). The purpose of this study is to determine the effectiveness of the larvicide application of temephos 1 % with membrane system using paris fabric, compared with the sowing system. The type of the research was an experiment employing post-test with control group design. The sample size of Aedes sp larvae was 1350 in the form of instar III and IV larvae or aged 4-6 days after hatching. The calculation of larvae mortality was conducted after 24 hours contact with temephos 1 % and was performed every two weeks in three months. The data obtained were analysed by using independent t-test at 95 % of confidence level. Theresults show that the mean mortality percentage due to the application of temephos 1 % with membrane system at bi-weekly observation (first to sixth) were 100 %, 94 %, 80 %, 68 %, 35 %, and 23 %, respectively; while the results from the sowing system as comparative positive control were 100 %, 86 % , 37 %, 23 %, 12 %, and 6 %, respectively. Descriptively, based on the graph of larvae mortality difference, it can be concluded that membrane system application is more effective than the sowing system. However, statistical analysis toward the mortality data of the bi-weekly observation from the first to the sixth found that the percentage difference is not significant (p-value = 0,298).